Helicobacter pylori 23S rRNA gene A2142G, A2143G, T2182C, and C2195T mutations associated with clarithromycin resistance detected in Sudanese patients - Aalaa Mahgoub Albasha; Maram M. Elnosh; Esraa Hassan Osman; Duha M. Zeinalabdin; Amira A. M. Fadl; Musa Abdalla Ali; Hisham N. Altayb (BMC Microbiology, 2021)
Abstract Background Clarithromycin resistant Helicobacter pylori (H. pylori) strains represent a worldwide health problem. These stains are usually carrying mutations within the 23S rRNA gene associated with clarithromycin resistance. This study aimed to detect H. pylori and clarithromycin resistant associated mutations from Sudanese patients with gastritis symptoms. Materials and methods Two hundred and eighty-eight gastric biopsies were collected using gastrointestinal endoscopy from patients with gastritis symptoms in different hospitals in Khartoum state. H. pylori was detected by PCR using primer targeting 16S rRNA. Then allele-specific PCR and DNA sequencing were used to screen for the presence of A2142G and A2143G point mutations. Results Out of 288 samples, H. pylori was detected in 88 (~ 30.6%) samples by 16 s RNA. Allele-specific PCR detected the variant A2142G in 9/53 (~ 17%) sample, while A2143G mutation was not found in any sample. The DNA sequencing revealed the presence of mutations associated with clarithromycin-resistance in 36% (9/25) of samples; the A2142G was present in one sample, A2143G in 5 samples and T2182C in 4 samples. Additionally, another point mutation (C2195T) was detected in 3 samples. There was no association of 23S rRNA gene point mutations with gender, age group, and patients’ geographical distribution. Conclusion This study revealed a high frequency (36%) of mutations associated with clarithromycin resistance using DNA sequencing of the 23S rRNA gene’s V domain. This information should be taken into consideration to avoid eradication therapy failing.